Instability and Chromatin Structure of Expanded Trinucleotide Repeats - Dion, Vincent (2009)
Trinucleotide repeat expansion underlies at least 17 neurologic diseases. In affected individuals, the expanded locus is characterized by dramatic changes in chromatin structure and in repeat tract length. Interestingly, recent studies show that several chromatin modifiers, including a histone acetyltransferase, a DNA methyltransferase, and the transcription factor CTCF can modulate repeat instability. Here, we propose that the unusual chromatin structure of expanded repeats directly impacts their instability. We discuss several potential models for how this might occur, including a role for DNA repair-dependent epigenetic reprogramming in increasing repeat instability, and the capacity of epigenetic marks to alter sense and antisense transcription, thereby affecting repeat instability.